2000
DOI: 10.1016/s0043-1354(99)00273-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of humic substance characteristics on UF performance

Abstract: AbstractÐThe role of humic substances in general and hydrophobicity of humic substances in particular on membrane permeate¯ux is unclear. The main goal of the present study is to evaluate the eect of fractionated humic substances on ultra®ltration (UF) performance. A commercial humic solution was subjected to a hydrophobic resin for fractionation of the hydrophobic and hydrophilic fraction. These fractions were further fractionated into dierent molecular wight groups, using gel ®ltration chromatography. The hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
79
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(85 citation statements)
references
References 26 publications
5
79
0
1
Order By: Relevance
“…The addition of 1.67 g l -1 PAC significantly reduced the high MW organics in the reactor, however, the further addition of another 1.67 g l -1 PAC did not reduce the amount of remaining high MW compounds any further. This might be because the remaining non-adsorptive substances have a low affinity for PAC, or that the carbon surface has been modified due to the adsorption of organics [20,21].…”
Section: Smp Production During Start-upmentioning
confidence: 99%
“…The addition of 1.67 g l -1 PAC significantly reduced the high MW organics in the reactor, however, the further addition of another 1.67 g l -1 PAC did not reduce the amount of remaining high MW compounds any further. This might be because the remaining non-adsorptive substances have a low affinity for PAC, or that the carbon surface has been modified due to the adsorption of organics [20,21].…”
Section: Smp Production During Start-upmentioning
confidence: 99%
“…However, natural organic matter (NOM) is often a major foulant during the ultrafiltration of surface water [1,2], since it contains a complex mixture of humic and fulvic acids, proteins, carbohydrates of various molecular sizes and functional groups [2][3][4][5], which can either bind to the membrane surface or support the development of microbiological fouling.…”
Section: Introductionmentioning
confidence: 99%
“…However, not all contaminants can be fully removed by the coagulation process, particularly biopolymers, such as polysaccharides and proteins [3][4][5]. In view of this, the combination of powder activate carbon (PAC) adsorption and UF has been reported to be more effective in the removal of organic contaminants, either as represented by total organic carbon or any other special pollutants [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, elimination of these humic substances during drinking water treatment is carried out by coagulation with hydrolyzed metal species such as aluminum and iron salts. However, the presence of uncoagulated humic materials in clarified water is responsible for reduced adsorption capacity in activated carbon beds, taste and odor of the finished water, membrane fouling, trihalomethane formation during chlorine disinfection, or biological regrowth in the distribution network [1][2][3]. Accord-ingly, considerable attention has been focused on the technologies and their own efficiency for eliminating these substances.…”
Section: Introductionmentioning
confidence: 99%
“…The United States Environmental Protection Agency has proposed that enhanced coagulation technology (ECT) is the best available technology (BAT) for the removal of these compounds [4][5][6]. Previous studies have paid close attention to the reaction behavior between FeCl 3 and humic acids [4][5][6], and it has been shown that FeCl 3 performs well in the removal of HA during enhanced coagulation processes. Recently, several studies have focused on the removal of HA and coagulated flocs with polyferric chloride (PFC), an inorganic polymer flocculant (IPF) that performs well in particle removal from natural water or wastewater.…”
Section: Introductionmentioning
confidence: 99%